A Conceptual modelling of QOS’ Web Service Framework - Charoenporn, Pattama; ., . (International Journal of Engineering and Technology, 2018)
The evolution of web service technologies is well known in many organizations. When many organizations want to develop our business, they will add new services in their businesses policy, these additions may help the organization to increase some policy but it is difficult to implement some requirements. To solve this problem, we present the new paradigm of QOS for develop web service that is the procedure to implement web service and help developer to create service appropriate each business process. This conceptual of modelling based on LSS and BWW framework and under business practice guideline the example is Cobit and ITIL for approximate each of business process. In success, we illustrate our approach by class diagram that design under conceptual of modelling quality of service for web service and implement web service for test this idea. Then we choose 2 scenarios in different combination of QoS requirements for test, the results show that this technique is satisfy for choose and we think this paper can be guideline for researcher in the future.Â Â